RESPONSIVITAS PELAYANAN PUBLIK DALAM MENANGANI KELUHAN PELANGGAN DIPERUSAHAAN DAERAH AIR MINUM (PDAM) SURYA SEMBADA KOTA SURABAYA - ANNISA FITRIANY Z. (Publika, 2015)
Responsiveness of public services is a testament to government agencies are able to recognize the needs of people in line with expectations, demand, and aspirations of the people. As one of the government agencies, Perusahaan Daerah Air Minum (PDAM) Surya Sembada Kota Surabaya must be able to recognize the needs of the people are realized through customer complaints submitted. Their complaint submitted indicates that the service provided has not met the expectations of the people. As evidence of the responsibility for the quality of service provided, Perusahaan Daerah Air Minum (PDAM) Surya Sembada Kota Surabaya need to show their responsiveness in customer complaints handling. The aim of this study to describe the resonsiveness of public services in customer complaint handling in Perusahaan Daerah Air Minum (PDAM) Surya Sembada Kota Surabaya. Type of this research used in this study is a qualitative descriptive. As for the focus of this research is an indicator of responsiveness by Zeithaml dkk (1990), which responds to every customer who wants to get service, the officers doing services quickly, the officers doing the right services, the officers doing services carefully, the officers doing services with the right timing, and all complaints responded by the officers. Research subjects in this study was taken by using purposive sampling techniques. Data collection techniques used were interviews, observation, and documentations. Data obtained will be analyzed using an interactive model of data analysis techniques. The result showed that four of the six indicator used, which responds to every customer who wants to get service, the officers doing services quickly, the officers doing services carefully, and the officers doing services with the right timing are already good. While the other two have, which the officers doing the right services and all complaints responded by the officers are not good yet. It is seen from the officers do not complaint handling in accordance with the previously reported and complaints submitted have not responded well. Advice that can be given is the officers need to be more carefull in complaint handling in accordance with that reported and Perusahaan Daerah Air Minum (PDAM) Surya Sembada Kota Surabaya expected to coordinate with technical personnel in order to better be able to quickly respond to cuctomer complaints and handled. Keyword: Responsiveness, Public Service, Customer Complaints